DIAGNÓSTICO DAS PRÁTICAS DE MELIPONICULTURA: a criação de Uruçu Cinzenta (Melipona fasciculata, SMITH 1854, APIDAE: MELIPONINI) na comunidade de Tamatateua (Bragança-PA) - MONTEIRO, Gerson Piedade (2024)
The present work had as aim to describe the rearing techniques of the Uruçu Cinzenta (Melipona fasciculata, Smith, 1854), a native stingless bee species, kept by the small farmers of the community of Tamatateua, municipality of Bragança-Pa. The data collection was carried out through interviews with 22 (twenty two) local creators, with the questionnaires application, containing questions pre-established, during the period of june to october of 2015, including the following requisites: The form as these bees are created; The form of acquisition of colonies; Identification of the hive models used; Description of the capture techniques and multiplication of colonies; Knowledge of the creators about the flora meliponicola; The aim of the rearing, and the forms of packaging honey. The results demonstrate that the practices used by these farmers are typically empirical, rustic and traditional, passed on between the creators orally and with the main intention of getting the honey. Stingless bee farming is still not widespread among people, making it necessary to access the farmers and discuss from their experiences ways to improve stingless bee farming in the community, emphasizing the relation with the environment, the adhesion of sustainable practices, keeping in mind the objective of generating labor occupation, as an extra income source and stimulating the consumption of stingless bee products.